The Japanese Compound Verb ~ kakeru (~ ã‹ã‘ã‚‹): It's Meaning and Formation - Taulia, Taulia; Gapur, Abdul (International Journal of Culture and Art Studies, 2022)
This study examines "~kakeru (ï½žã‹ã‘ã‚‹) Compound Verbs in Japanese Sentences." This study describes the structure and meaning of the compound verb kakeru in Japanese sentences. The data used by the researcher come from diverse sources, including books, dictionaries, and sentences written by the researchers themselves. It utilizes library resources to collect the necessary data. Then, the form and meaning of the compound verb kakeru are determined using the distributional method and the basic direct element technique. Based on the data analysis, it can be concluded that the meaning describes the activity's initiation and its state. In addition to being attached to activity verbs and punctual verbs, the form of the compound verb kakeru can also be attached to stative verbs. In sentences containing the compound verb kakeru, that state just before an activity begins and activities that have been ongoing for some time.